SOCIALIZATION OF CLEAN WATER FACILITIES IN NATIVE KUTAGALUH VILLAGE LAWE BULAN DISTRICT ACEH TENGGARA DISTRICT - Muhammad Yassir; Orbit Irwansyah; Ladipin; Muhammad Tahir; Muridha Hasan (CV. Naskah Aceh, 2024)
Community Service Activities were carried out in Kuta Galuh Asli Village, a village located in Lawe Bulan District, Southeast Aceh Regency, the activity was carried out for one day by providing direction to the community about the need for clean water facilities, especially for consumption, starting from drinking, bathing, washing and other activities considering the importance of clean water to support all aspects of life. The source of data obtained from direct interviews with the community in Kutagaluh Galuh Village, the community said that it was difficult to need clean water to be used as a source of household needs and based on observations or observations at the location of the residential area that the availability of water was constrained to be obtained in the village, so it is necessary to understand and identify the need for clean water for consumption needs in the Kuta Galuh Asli Village community, Southeast Aceh Regency. The strategy for utilizing clean water in Kuta Galoh Asli Village, Southeast Aceh Regency currently requires PDAM (Regional Drinking Water Company) and the provision of water pump assistance to the community and also requires long pipes to connect the water in the river to flow to the residents' homes